Comparative Study between Slow Shock Wave Lithotripsy and Fast Shock Wave Lithotripsy in the Management of Renal Stone - Paul, Deb Prosad; Das, Debashish; Rahman, ASM Zahidur; Bhuiyan, AKM Zamanul Islam (Journal of Enam Medical College, 2013)
Background: Renal calculi are frequent causes of ureteric colic. Extracorporeal shock wave lithotripsy is the most common treatment of these stones. It uses focused sound waves to break up stones externally. Objective: To compare the efficiency of slow and fast delivery rate of shock waves on stone fragmentation and treatment outcome in patients with renal calculi. Materials and Methods: This prospective study was done in the department of Urology, National Institute of Kidney diseases and Urology, Sher-e-Bangla Nagar, Dhaka from July 2006 to June 2007. Total 90 patients were treated using the Storz Medical Modulith ® SLX lithotripter. Patients were divided into Group A, Group B and Group C each group having 30 subjects. Group A was selected for extracorporeal shockwave lithotripsy (ESWL) by 60 shock waves per minute, Group B by 90 shock waves per minute and Group C by 120 shock waves per minute. Results: Complete clearance of stone was observed in 24 patients in Group A and 13 patients in both Group B and Group C in first session. In Group A only 3 patients needed second session but in Group B and Group C, 12 and 8 patients needed second session. In Group A only one patient needed third session but third session was required for 3 patients in Group B and 5 patients in Group C for complete clearance of stone. In Group A, subsequent sessions were performed under spinal anesthesia and in Group B under sedation and analgesia (p>0.001). Mean number of sessions for full clearance of stones in group A was 1.37 ± 0.85, in Group B was 1.8 ± 0.887 and in Group C was 2.0 ± 1.083. Significant difference was observed in term of sessions among groups (p>0.05). In first follow-up, complete clearance of stones was seen in 24 patients in Group A and 13 in both Group B and Group C. In second follow-up, 3 patients in Group A, 12 in Group B and 8 in Group C showed complete clearance of stones. It was observed that rate of stone clearance was higher in Group A than in Group B and Group C. Multiple logistic regression analyses revealed that slow delivery rate (60 SW/min) as well as age (younger), symptom (painful) at onset, stone location (upper and middle calyx) and size (small) were independent prognostic factors determining stone clearance after ESWL of renal stone. Conclusion: Slow rate shock wave delivery improves efficacy of ESWL treatments of renal stone and decreased number of sessions, shock waves and treatment time. DOI: http://dx.doi.org/10.3329/jemc.v3i1.13870 J Enam Med Col 2013; 3(1): 24-28